Double-Proton-Transfer Processes in Dithiooxamide: UV-Induced Dithione → Dithiol Reaction and Ground-State Dithiol → Dithione Tunneling - Lapinski, Leszek (2004)
Dithiooxamide [rubeanic acid, NH2C(S)C(S)NH2)] monomers were studied by FTIR spectroscopy combined with the low-temperature matrix-isolation technique. The most stable dithione−diamino tautomer of the compound was exclusively observed in argon matrixes immediately after deposition. Upon UV (λ > 345 nm) irradiation the dithione−diamino form transformed, by a double-proton transfer, into the dithiol−diimino tautomer. Theoretically supported analysis of the infrared spectrum emerging upon UV irradiation allowed identification of one of the conformers of the dithiol−diimino tautomer as the dominating photoproduct. Smaller quantities of other conformers of the dithiol−diimino tautomer were also found to be photogenerated. For the UV-irradiated matrix kept subsequently at 10 K and in darkness, a dithiol−diimino → dithione−diamino tautomerization leading to partial recovery of the initial form of the compound was observed. The only possible mechanism of this ground-state transformation at cryogenic temperature is synchronous double-proton tunneling. The experimentally obtained time constant of this process was 18 h.